Preschoolers consider the recipient's merit and the role of allocator when distributing resources - Wong, M; Nunes, T (Early Childhood Australia Inc., 2014)
This study assessed the effects of contextual factors embedded in stories on children's conception of the fair allocation of resources. Previous studies on children's concept of distributive justice led to the conclusion that preschool children use only the equality rule to allocate resources among recipients and are unable to use the equity rule to reward effort or task performance. We hypothesised that children's allocation decisions can include an equity rule, depending on the context of resource allocation. Five-year-olds' allocation decisions varied with contextual factors, supporting the view that cognitive development takes place in context. They used the equity rule more in the family context and preferred the equality rule in the school context. Implications for classroom practice are discussed.